Acute gastroenteritis in infants (analysis of 483 cases treated in an infant’s ward) - Hasanoğlu, Enver; Berkel, A. İzzet (The Turkish Journal of Pediatrics, 1976)
A total of 483 infants between 1 day and 3 years of age who were admitted to the infant contagion ward of Hacettepe Children’s Hospital because of acute gastroenteritis within a period of 12 months were studied. The seasonal incidence, types of dehydration, associated conditions, bacteriologic studies and factors influencing the course and outcome were analysed. Acute gastroenteritis was mostly observed in the summer and autumn months. The majority of the affected infants were younger than 6 months and isotonic type dehydration was the most common type. Infantile marasmus, bronchopneumonia, anemia, sepsis and urinary tract infections were the commonly associated conditions. Throat cultures disclosed normal bacterial flora in the majority. In our series, viral studies were not carried out, but 97 % of the patients had non-invasive E. Coli in their stools. About 20 % of the stool cultures grew from bacterial pathogens including salmonella, EPEC, klebsiella, shigella and others, in decreasing frequency.